Study on Performance of Mesoscopic Impactor Filters for Aerosol Removal - Wei Zhang; Fenglei Niu; Shiji Wang; Haonan Wang; Zhangpeng Guo (Science and Technology of Nuclear Installations)
The mesoscopic impactor filter is designed to filtrate aerosols in the containment, which has not only high collection efficiency but also small flow resistance. In this paper, the influence of structural parameters and working parameters of the inertial impactor on collection performance is studied by the computational fluid dynamic (CFD) method. Under the small Reynolds number, the laminar model is used to simulate the continuous phase, and the discrete phase model (DPM) is used to track the trajectory of the particle. Based on the response surface methodology (RSM), the prediction model of collection efficiency and pressure drop is obtained, which will provide a reference for the design and manufacture of the filter in the future.